Morphological changes of ZnO nanostructures upon addition of tannic acid - Aqilah, Kamaruzaman; Nurul Akmal, Che Lah (Penerbit UMP, 2021)
Due to their potential as a good semiconductor, Zinc Oxide nanostructures (ZnO) have received abundant of interest. In this analysis, ZnO nanostructures are synthesized by a hydrothermal process that uses a green method of synthesis completely aided by Tannic Acid (TA). The mean diameter of ZnO nanostructures are observed to increase with addition of TA due to the aggregation that occurred from the influenced of acidic medium. The morphological properties are discussed based on the TEM images which indicated the average size of 8nm for ZnO NPs and 18-23nm for ZnO-TA nanostructures obtained, respectively.